Effects of Short-Term Cognitive Remediation on Cognitive Dysfunction in Partially or Fully Remitted Individuals with Bipolar Disorder: Results of a Randomised Controlled Trial. - Kirsa M Demant; Maj Vinberg; Lars V Kessing; Kamilla W Miskowiak (PLoS ONE)
Introduction Cognitive dysfunction is common in bipolar disorder (BD) but is not sufficiently addressed by current treatments. Cognitive remediation (CR) may improve cognitive function in schizophrenia but no randomised controlled trial has investigated this intervention in BD. The present study aimed to investigate the effects of CR on persistent cognitive dysfunction in BD. Method Patients with BD in partial remission with cognitive complaints were randomised to 12 weeks group-based CR (n=23) or standard treatment (ST) (n=23). Outcomes were improved verbal memory (primary), sustained attention, executive and psychosocial function (secondary) and additional measures of cognitive and psychosocial function (tertiary). Participants were assessed at baseline and weeks 12 and 26. Results Of the 46 randomised participants five dropped out and one was excluded after baseline. CR (n=18) had no effect on primary or secondary measures of cognitive or psychosocial function compared with ST (n=22). However, CR improved subjective sharpness at week 12, and quality of life and verbal fluency at week 26 follow-up (tertiary outcomes). Although the trial turned out to have suboptimal statistical power for the primary outcome analysis, calculation of the 95% confidence interval showed that it was highly unlikely that an increase in sample size would have rendered any beneficial effects of CR vs. ST on the verbal memory. Conclusions Short-term group-based CR did not seem to improve overall cognitive or psychosocial function in individuals with BD in full or partial remission. The present findings suggest that that longer-term, more intensive and individualised CR may be necessary to improve cognition in BD. Trial registration ClinicalTrials.gov NCT01457235.